Could symptom burden predict subsequent healthcare use in patients with end stage kidney disease on hemodialysis care? A prospective, preliminary study. Issue 1 (1st January 2020) - Zhang, Jing C.; El-Majzoub, Salam; Li, Madeline; Ahmed, Tibyan; Wu, Joyce; Lipman, Mark L.; Moussaoui, Ghizlane; Looper, Karl J.; Novak, Marta; Rej, Soham; Mucsi, Istvan
Abstract: Context: Patients treated with maintenance hemodialysis experience significant symptom burden resulting in impaired quality of life. However, the association of patient reported symptom burden and the risk of healthcare use for patients with end stage kidney disease on hemodialysis has not been fully explored. Objectives: To investigate if higher symptom burden, assessed by the Edmonton Symptom Assessment System-revised (ESASr), is associated with increased healthcare use in patients with end stage kidney disease on hemodialysis. Methods: Prospective, single-center, study of adult patients on HD. Participants completed the ESASr questionnaire at enrollment. Baseline demographic, clinical information as well as healthcare use events during the 12-month following enrollment were extracted from medical records. The association between symptom burden and healthcare use was examined with a multivariable adjusted negative binomial model. Results: Mean (SD) age of the 80 participants was 71 (13) years, 56% diabetic, and 70% male. The median (IQR) dialysis vintage was 2 (1–4) years. In multivariable adjusted models, higher global [incident rate ratio (IRR) 1.02, 95% confidence interval (CI) 1.00–1.04, p  = .025] and physical symptom burden score [IRR 1.03, CI 1.00–1.05, p  = .034], but not emotional symptom burden score [IRR 1.05, CI 1.00–1.10, p  = .052] predicted higher subsequent healthcare use. Conclusions: Our preliminary evidence suggests that higher symptom burden, assessed by ESASr may predict higher risk of healthcare use amongst patients with end stage kidney disease on hemodialysis. Future studies need to confirm the findings of this preliminary study and to assess the utility of ESASr for systematic symptom screening.